1993
DOI: 10.1007/bf00926359
|View full text |Cite
|
Sign up to set email alerts
|

Role of extracellular matrix proteins in heart function

Abstract: The cardiac interstitium is populated by nonmyocyte cell types including transcriptionally active cardiac fibroblasts and endothelial cells. Since these cells are the source of many components of the cardiac extracellular matrix, and because changes in cardiac extracellular matrix are suspected of contributing to the genesis of cardiovascular complications in disease states such as diabetes, hypertension, cardiac hypertrophy and congestive heart failure, interest in the mechanisms of activation of fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
74
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(78 citation statements)
references
References 161 publications
2
74
0
2
Order By: Relevance
“…Protein synthesis may be affected in all cell types, while cell division has been found to occur in certain cells of different tissues: fibrocytes in the LV (Pelouch et al 1994), smooth muscle cells and fibrotic cells in the aorta, mesangial cells in the kidney (Hropot et al 1994), and conceivably fibrocytes in the brain. In our previous work (Bab al et al 1997), proliferation cell nuclear antigen immunohistochemistry indicated positive cells in the fibrotic tissue of the myocardium as well as in the media of coronary arteries and aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Protein synthesis may be affected in all cell types, while cell division has been found to occur in certain cells of different tissues: fibrocytes in the LV (Pelouch et al 1994), smooth muscle cells and fibrotic cells in the aorta, mesangial cells in the kidney (Hropot et al 1994), and conceivably fibrocytes in the brain. In our previous work (Bab al et al 1997), proliferation cell nuclear antigen immunohistochemistry indicated positive cells in the fibrotic tissue of the myocardium as well as in the media of coronary arteries and aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The myocardial ECM directs contractile force generated by cardiomyocytes and sustains shear stress generated by cardiomyocytes. In addition, the myocardial ECM produces and maintains certain levels of a variety of growth factors, as well as modulates cell proliferation and differentiation, ECM synthesis and remodeling [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of NO synthesis has been E R6sen et al: Endothelial relaxation is disturbed in diabetes shown to lead to an activation of the sympathetic nervous system [26], which is a frequent complication in human and experimental diabetes [27]. It has been suggested, furthermore, that in diabetes an activation of the sympathetic nervous system contributes to myocardial damage either by the generation of cytotoxic free radicals derived from catecholamines [28] or by induction of hypertrophy and growth factors resulting in an increased expression of collagen in myocardium [27,29,30]. Prevention of NO inactivation by oxidative stress is therefore expected to protect the heart in diabetes by at least two different mechanisms: directly, by restoring the vasodilatory effect of NO and indirectly, by prevention of a cascade of events associated with the excessive activation of the sympathetic nervous system.…”
mentioning
confidence: 99%